(untitled) (New York,Cambridge, UK, 2004)
Scientists have only recently come to believe that the presence of ice is widespread in our solar system. Focusing on the occurrence and significance of water ice, and ices formed by other materials, this volume considers the implications of the reservoirs of water ice for the presence of life elsewhere in our solar system, and for habitability by human explorers who may venture to these distant worlds in the future. Patricia Ann Dasch is a consultant in the space industry specializing in policy and public outreach issues. She has written, published, and broadcast on a wide variety of space-related issues for the past twenty years. From 1997-2000 she served as Executive Director of the Washington, DC-based National Space Society
Keywords: Solar system,Ice,Hệ mặt trời